2022
DOI: 10.3390/ijerph19063195
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care in Older People with Multimorbidities: A Scoping Review on the Palliative Care Needs of Patients, Carers, and Health Professionals

Abstract: Although numerous studies have been conducted previously on the needs of cancer patients at the end of their life, there is a lack of studies focused on older patients with non-oncological complex chronic multipathologies. Examining these needs would help to gain a greater understanding of the profile of this specific population within the palliative care (PC) pathway and how the health and care systems can address them. The aim of this review was to identify the needs influencing PC among older patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 94 publications
(473 reference statements)
1
8
0
Order By: Relevance
“…There is increasing evidence that the implementation of palliative care generates clinically significant improvements in the patient’s quality of life [ 11 ]. The findings of this study suggest that there are unmet needs of older patients with multimorbidities and their families/carers for timely palliative care, including feeling uncertain and a sense of fear, poor awareness and knowledge on palliative care in non-malignant settings and the desire for improved physical, psychosocial and financial status as suggested in previous studies [ 12 , 16 , 17 ]. It would be interesting to relate these needs to factors such as frailty in these patients.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…There is increasing evidence that the implementation of palliative care generates clinically significant improvements in the patient’s quality of life [ 11 ]. The findings of this study suggest that there are unmet needs of older patients with multimorbidities and their families/carers for timely palliative care, including feeling uncertain and a sense of fear, poor awareness and knowledge on palliative care in non-malignant settings and the desire for improved physical, psychosocial and financial status as suggested in previous studies [ 12 , 16 , 17 ]. It would be interesting to relate these needs to factors such as frailty in these patients.…”
Section: Discussionmentioning
confidence: 54%
“…Solid evidence on early identification, needs assessment and mapped palliative care pathways to provide symptom management and the support to patients and their families is still lacking [ 12 ]. To improve the experience of multimorbid patients receiving palliative care and their families requires us to find out what their experience has been in the health system and the gaps or needs they have identified in their care.…”
Section: Introductionmentioning
confidence: 99%
“…75 In addition to management of their medical illnesses, patients with multimorbidity often have unmet emotional, informational, spiritual, cultural, social, and caregiver needs that may require specialist PC intervention. 74,76…”
Section: Discussionmentioning
confidence: 99%
“…Matching our study’s findings, Gothe and colleagues showed an average age of patients receiving palliative care of 77 years [ 33 ]. Demographic change, accompanied by steadily increasing life expectancy, will not only bring increasing multimorbidity, but will also require greater demand for palliative care [ 34 ]. Consequently, palliative care services have to be continuously improved and expanded, especially addressing the diverse needs of the elderly population in the future.…”
Section: Discussionmentioning
confidence: 99%